2010
DOI: 10.1177/1545968310382424
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Effective Connectivity Changes Following Explicit-Memory Training for Face–Name Pairs in Patients With Mild Cognitive Impairment

Abstract: Background Mild cognitive impairment (MCI) is often a precursor to Alzheimer’s disease. Little research has examined the efficacy of cognitive rehabilitation in patients with MCI, and the relevant neural mechanisms have not been explored. We previously reported on a pilot study showing the behavioral efficacy of cognitive rehabilitation using mnemonic strategies for face-name associations in patients with MCI. Here we used functional magnetic resonance imaging (fMRI) to test whether there were training-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
143
2
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 64 publications
19
143
2
11
Order By: Relevance
“…regions (Hampstead, Stringer, Stilla, Deshpande, et al, 2011) as well as a partial restoration of hippocampal activation in those with MCI (Hampstead, Stringer Stilla, Giddens, & Sathian, 2012). Belleville and colleagues (2011) also suggested that the right temporoparietal junction may play a compensatory role during strategy use in MCI patients.…”
Section: Memory Rehabilitation In MCI 139mentioning
confidence: 99%
“…regions (Hampstead, Stringer, Stilla, Deshpande, et al, 2011) as well as a partial restoration of hippocampal activation in those with MCI (Hampstead, Stringer Stilla, Giddens, & Sathian, 2012). Belleville and colleagues (2011) also suggested that the right temporoparietal junction may play a compensatory role during strategy use in MCI patients.…”
Section: Memory Rehabilitation In MCI 139mentioning
confidence: 99%
“…In a study conducted by Hampstead et al (2011), fMRI was used to test whether there were training-specific changes in the activation and connectivity within memory-related areas of patients with multidomain MCI. The findings suggested that the effectiveness of explicit memory strategy training in subjects with MCI (associative memory) is associated with training-specific increases in activation and connectivity across a distributed neural system, which included areas involved in explicit memory function.…”
Section: Memory Interventions In Mild Cognitive Impairment and Alzheimentioning
confidence: 99%
“…Hence, some authors have proposed modified versions such as biopsycosocial or psychobiosocial therapies. 2,3 Functional magnetic resonance imaging (fMRI), due to its capacity to monitor neural circuits reorganization, has been recently introduced to evaluate the efficacy of these nonpharmacological treatments (see Cramer et al 4 for a review), also including treatments for amnestic mild cognitive impairment (MCI) 5 and AD. 6 Cognitive stimulation (CS) is probably the most widespread and well-studied technique in this field, but it is still a matter of debate whether this therapy is able to slow down the disease course.…”
Section: Introductionmentioning
confidence: 99%